2016
DOI: 10.1016/j.atherosclerosis.2015.10.108
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine intake and high trimethylamine N-oxide plasma levels correlate with low aortic lesions in ApoE−/− transgenic mice expressing CETP

Abstract: These findings suggest that TMAO slows aortic lesion formation in this mouse model and may have a protective effect against atherosclerosis development in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 56 publications
3
115
0
5
Order By: Relevance
“…A follow-up study found that none of three examined FMO3 polymorphisms predispose to hypertension in a sample of several hundred Caucasian patients, but also noted that severe, highly penetrant loss-of-function mutations could "unmask pressor effects of variation in other drug metabolizing enzymes previously buffered by FMO3" (51). At least two more recent studies are consistent with TMAO production having a reactive, protective function in response to CVD pathology (52,53), with one of these studies asserting that TMAO is, in fact, protective against CVD risk (53). What is clear from these publications is that TMAO is a molecule of great interest due to its diverse functions including osmolyte, chemical chaperone, reactive oxygen species scavenger, and now, potential risk factor (54).…”
Section: Atherosclerosis and Cardiovascular Disease (Cvd)mentioning
confidence: 57%
“…A follow-up study found that none of three examined FMO3 polymorphisms predispose to hypertension in a sample of several hundred Caucasian patients, but also noted that severe, highly penetrant loss-of-function mutations could "unmask pressor effects of variation in other drug metabolizing enzymes previously buffered by FMO3" (51). At least two more recent studies are consistent with TMAO production having a reactive, protective function in response to CVD pathology (52,53), with one of these studies asserting that TMAO is, in fact, protective against CVD risk (53). What is clear from these publications is that TMAO is a molecule of great interest due to its diverse functions including osmolyte, chemical chaperone, reactive oxygen species scavenger, and now, potential risk factor (54).…”
Section: Atherosclerosis and Cardiovascular Disease (Cvd)mentioning
confidence: 57%
“…In addition, they also showed that higher TMAO level predicted increase risks for prevalent cardiovascular disease and incident adverse cardiac events. On the other hand, other reports demonstrated that oral L‐carnitine supplementation increases TMAO but reduces markers of vascular injury in hemodialysis patients34 or L‐carnitine intake and high TMAO plasma levels correlate with low aortic lesions 35. Therefore, the link between gut microbiota metabolism of L‐carnitine and cardiovascular disease risk has generated much debate over the utility of supplemental intake of L‐carnitine.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthy to note that ApoE-/-animal model, used in these studies is characterized by diverse risk factors on the development of atherosclerosis also because of the absence of cholesterylester transfer protein (CETP) in mouse plasma compared with the human one [28]. Conversely, in ApoE-/-mouse expressing hCETP (containing human CETP gene) TMAO plays a protective role in aortic lesion formation [29].…”
Section: Discussion/conclusionmentioning
confidence: 99%